The Effect of Project-Based Learning (PJBL) on The Critical Thinking Ability of Science - Rahman, Saenal; Iswatiningsih, Daroe; Inganah, Siti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This research investigates the effect of the Project-Based Learning (PjBL) model on the critical thinking abilities of third-grade students in the Natural and Social Sciences (IPAS) subject at MI Muhammadiyah Romang Lompoa. The study adopts a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of two classes: an experimental group taught using the PjBL model and a control group receiving conventional instruction, each comprising 20 students. Data were collected through a validated essay-based critical thinking test. Statistical analysis using a t-test was conducted to examine differences between the pre-test and post-test results of both groups. The findings reveal that students' critical thinking abilities significantly improved after the PjBL model was implemented, as seen by the experimental class's higher mean post-test scores than the control group. Therefore, the study concludes that PjBL has a positive and significant impact on enhancing students’ critical thinking skills in science-related learning materials.